IMPACT OF ECO-FRIENDLY PROCUREMENT POLICIES ON THE EFFICIENCY OF PUBLIC ENTERPRISES IN RWANDA - Kabagambe, Harriet; Ndolo, Kipkorir (Ayden International Journal of Banking, Finance and Technology, 2024)
Green procurement has become a critical strategy for organizations that aim to achieve environmental sustainability and enhance their performance in the face of increasing competition, market pressure, and regulations. This study aimed to investigate the influence of green procurement management policy on the performance of state corporations in Rwanda. Using a descriptive research design, the study obtained a sample of 119 respondents from a target population of 238 through stratified random sampling. Primary data was collected using a structured questionnaire, and quantitative data was analyzed using descriptive and inferential statistics, including multiple regression analysis to determine the relationship between study variables. The study found that green procurement management policy was statistically significant in enhancing the performance of state corporations in Rwanda (β = 0.531, P = 0.001). The study recommends that state corporations should adhere to green procurement management policies to enhance their performance and inspire other organizations to adopt green practices.